Association of Orai1 and Peizo1 genes expression with cellular proliferation, metastasis and angiogenesis biomarkers in colon tumor biopsies of CRC patients: Calcium signaling and angiogenesis in CRC progression - Awla, Farhang; Othman, Goran (Cellular and Molecular Biology, 2023)
Colon cancer is a complex malignancy characterized by intricate molecular interactions that influence its progression. This study investigates the role of calcium channel gene expression (ORAI1 and Piezo1) and their interplay with angiogenesis-related genes (VEGFA, CCL3, and NF-KB1) in colon cancer tissue biopsies. Additionally, we explore the mutation profiles of pivotal oncogenes (KRAS, PI3KCA, and BRAF) and their potential correlations with calcium channel and angiogenesis-related gene expression. The results indicate significant upregulation of ORAI1 and Piezo1, suggesting their involvement in colon cancer pathogenesis. Correlations between ORAI1 and VEGFA/CCL3 highlight potential crosstalk between calcium signaling and angiogenesis. The mutation analysis identifies prevalent oncogenic mutations, while intriguing connections between gene expression and oncogenic mutations emerge. Notably, mutant KRAS exon 2 samples exhibit elevated CCL3 and VEGFA expression, suggesting a nuanced link between specific KRAS mutations and the tumor microenvironment. These findings illuminate the intricate molecular landscape of colon cancer and emphasize the potential roles of calcium channels, angiogenesis-related genes, and oncogenic mutations as prognostic markers and therapeutic targets.